Methodological proposal for strengthening the development of oral communicative competence in english for students of eleventh grade at Francisco Morazán High School - Moreno, Susana; Fanny Pinto; Vargas, Víctor (David, Panamá : UDELAS, 2010)
Foreign language teaching responds to the multilateral and integral comprehensive training of human beings for acquiring a scientific world view, to be able to interpert and creatively transform the reality of a place in times of globalized crisis.
INDEX DEDICATORY ACKNOWLEDGMENT INTRODUCTION I. CHAPTER : STATEMENT OF THE PROBLEM II. CHAPTER: THEORICAL FRAMEWORK Communicatiave competence definition IB learner profile language perspective Charactgeristics of communicative competence Kinds of communicative competence Fluency Criteria to assess oral communicative competence Didatc approaches used by teachers Kinds of teaching methods Techniques used by teacher to develop oral communication Motivation to develop oral communication definition types of motivations Factors that influence on students' motivation development Teacher´s role for motivating students Principles to encourage students to speak english Language barriers definition Kinds of factors Teachers' role Common classroom problems III CHAPTER: METHODOLOGICAL FRAMEWORK IV CHAPTER: ANALYSIS OF THE RESULTS V CHAPTER: METHODOLOGICAL PROPOSAL CONCLUSIONS RECOMMENDATIONS REFERENCES ANNEX
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; FACULTAD DE CIENCIAS SOCIALES; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; FRANCISCO MORAZAN HIGH SCHOOL